Methods of Increasing Labour Productivity in Service Enterprise - Skąpska, Elżbieta; Rollnik-Sadowska, Ewa; Konicka, Ewelina (Olsztyn Economic Journal, 2017)
In the era of innovation resulting from intense competition on a global scale, a modern enterprise, especially a service one, needs to keep pace with the changing market conditions. One of the requirements, under the process of “technologization” of economic activities that determines the survival and development of an enterprise, is the ability to increase the level of labour productivity. Identifying the determinants of labour productivity in the enterprise, to a large extent, affects the building of its competitive position and market advantage. As service companies are exposed to substantial uncertainty and risk, they are particularly focused on finding ways to rationalize costs and increase efficiency. The aim of this article is to present the methods of increasing labour productivity in a modern service enterprise. The research methods undertaken include an analysis of secondary sources as well as a case study of a specific service enterprise.